Impact of additives on thermally-induced trans isomers in 9c, 12c linoleic acid triacylglycerol. (1st May 2015) - Guo, Qin; Ha, Yiming; Li, Qingpeng; Jin, Jing; Deng, Zhaoxuan; Li, Yongfu; Zhang, Songshan
Highlights: Thermally-induced trilinolein produce twice the amount of trans NLA compared to CLA. N2 stream reduces the amount of both trans NLA and CLA products. TBHQ is an effective additive for reducing trans NLAs and inducing CLAs. Glutathione andl -cysteine at 0.1% may be also used as additives for frying oil. Fe 3+ and Al 3+ ions derived from oils can reduce trans NLAs and induce CLAs. Abstract: Trilinolein, with or without additives, was placed in glass ampoules and subjected to thermal treatment at 180 °C or 240 °C for 8 h. Thermal treatment of trilinolein at 180 °C and 240 °C produced twice the amount of trans nonconjugated linoleic acids (NLAs) compared to conjugated linoleic acids (CLAs), and nitrogen stream reduced the amount of both trans NLA and CLA products. The presence of additives resulted in the suppression or induction of trans NLAs and CLAs, depending on the type of additive, the concentration of the additive, and the heating temperature. Our analysis indicates that TBHQ is an effective additive for reducing trans NLA formation and inducing trans CLA formation in frying oil. Glutathione andl -cysteine at 0.1% may also be used as additives for frying oil. At suitable concentrations, Fe 3+ and Al 3+ ions derived from oils can reduce trans NLAs and induce trans CLAs during frying.